2023
DOI: 10.1002/jcla.24885
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Helicobacter pylori: From potential biomolecular mechanisms to clinical practice

Abstract: Helicobacter pylori (H. pylori) is a gram-negative microaerobic bacterium that is a common pathogen widely distributed around the world, especially in developing countries. 1 According to statistics from recent years, the H. pylori infection rate in developing countries exceeds 50%. 2 In West Asia, Africa, and South America, the H. pylori infection rate has been reported to be as high as 66.6%, 70.1%, and 69.4%, respectively. 3 H. pylori infection causes persistent damage to human gastric mucosa, leading to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 171 publications
0
13
0
Order By: Relevance
“…Other genes assumed to be involved in CLR resistance are rpl22 and infB. In fact, several point mutations in infB (C718T, A1899G, G160A, G60A) as well as 9-bp insertion and/or 3-bp deletion in rpl22 genes have been described, which, in combination with 23S rRNA mutations, are predicted to increase the resistance level of H. pylori isolates [11,37]. Interestingly, no indels in rpl22 gene were detected in our study: instead, we found 3-bp deletion in infB gene primarily in CLR-susceptible isolates, but not signi cantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other genes assumed to be involved in CLR resistance are rpl22 and infB. In fact, several point mutations in infB (C718T, A1899G, G160A, G60A) as well as 9-bp insertion and/or 3-bp deletion in rpl22 genes have been described, which, in combination with 23S rRNA mutations, are predicted to increase the resistance level of H. pylori isolates [11,37]. Interestingly, no indels in rpl22 gene were detected in our study: instead, we found 3-bp deletion in infB gene primarily in CLR-susceptible isolates, but not signi cantly.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that OMPs are associated with macrolide resistance in Gram-negative bacteria. Lin et al (2023) suggested that the alteration of outer membrane proteins is a potential mechanism involved in CLR resistance development in H. pylori, but the speci c function and mechanism of action of these proteins need to be further studied [37]. Interestingly, Thompson et al (2003) showed the close coexpression of the cagA gene with the omp5 and omp29 genes, suggesting these OMPs are involved in the secretion and/or activation of CagA [38].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this bacterium has demonstrated resistance to multiple antibiotics, a phenomenon largely attributable to genetic mutations. These mutations not only confer resistance but may also enhance the virulence of the bacteria ( Lin et al., 2023 ). For instance, mutations in the 23S rRNA gene of H. pylori can impede the binding of clarithromycin to the ribosomal subunit, leading to resistance to this drug ( Albasha et al., 2021 ).…”
Section: H Pylori Vaccinementioning
confidence: 99%
“…When antibiotics are prescribed for non-bacterial infections or for conditions that do not require antibiotic treatment, the bene cial bacteria in the gut may be disrupted, leading to an increase in the growth of harmful bacteria such as H. pylori. Additionally, the overuse or misuse of antibiotics can lead to the development of antibiotic-resistant strains of bacteria, including H. pylori, which can be di cult to treat and can lead to more severe and potentially life-threatening infections (55). In addition to appropriate use of antibiotics, other strategies for managing and preventing H. pylori infection include lifestyle modi cations, such as maintaining a healthy diet and avoiding tobacco use, as well as the use of complementary therapies such as probiotics and certain dietary supplements, as discussed in previous answers.…”
Section: Lifestyle Modi Cationsmentioning
confidence: 99%